Professional orientation of a teacher in the context of STEAM education introduction and the prerequisites for STEAM competencies formation - Movmyga, Nataliia Yevhenivna; Demidova, Yulia; Polezhaieva, Olena Viktorivna (Національний технічний університет "Харківський політехнічний інститут", 2024)
The issue of teacher`s professional development in the context of STEAM education introduction is considered. Emphasis is put on the actualization of 4C method which is used to overcome the misunderstanding between the knowledge that students acquire in higher education institutions and the skills that employers expect from students. This method includes such main components as: communication skills, creativity, critical thinking and teamworking. The proposed recommendations for the development of STEAM competencies can contribute to the formation of professional success and development of innovative pedagogical experience of higher education institutions teachers. This research does not solve the problem of teacher`s professional development in the field under consideration and can be continued in analyzing its features depending on the professional area of study.

Розглянуто питання професійної спрямованості та розвитку педагога в умовах запровадження STEАМ-освіти. Зроблено акцент на актуалізації методу 4К, який використовується для подолання невідповідності між знаннями, які отримують студенти на етапі фахової підготовки і тими навичками, що очікують від студентів роботодавці. Цей метод включає в себе основні складові: комунікативні навички, креативність, критичне мислення та командну роботу. Запропоновані рекомендації розвитку STEAM компетентностей можуть сприяти формуванню професійної успішності та розвитку інноваційного педагогічного досвіду викладачів ЗВО. Дане дослідження не вичерпує проблему професійного розвитку педагога у розглянутій галузі та може бути продовжено у напрямі вивчення її особливостей залежно від фахових напрямків навчання.
Професійна спрямованість педагога в умовах запровадження STEАМ-освіти та особливості розвитку STEАМ компетентностей
Keywords: STEAM education; STEAM competence; transdisciplinary approach; competence approach; 4C formula; teacher professional development; communication skills; creativity; critical thinking; teamwork; definitions of STEM education; STEАМ-освіта; STEАМ-компетентність; трансдисциплінарний підхід; компетентнісний підхід; формула 4К; професійний розвиток педагога; комунікативні навички; креативність; критичне мислення; командна робота; дефініції STEАM-освіти